In Vitro and in Vivo Evidence for a Lack of Interaction with Dopamine D2 Receptors by the Metabotropic Glutamate 2/3 Receptor Agonists 1S,2S,5R,6S-2-Aminobicyclo[3.1.0]hexane-2,6-bicaroxylate Monohydrate (LY354740) and (−)-2-Oxa-4-aminobicyclo[3.1.0] Hexane-4,6-dicarboxylic Acid (LY379268) - Fell, Matthew J.; Perry, Kenneth W.; Falcone, Julie F.; Johnson, Bryan G.; Barth, Vanessa N.; Rash, Karen S.; Lucaites, Virginia L.; Threlkeld, Penny G.; Monn, James A.; McKinzie, David L.; Marek, Gerard J.; Svensson, Kjell A.; et al. (The Journal of pharmacology and experimental therapeutics, 2009)
Some recently published in vitro studies with two metabotropic glutamate 2/3 receptor (mGluR2/3) agonists [(−)-2-oxa-4-aminobicyclo[3.1.0] hexane-4,6-dicarboxylic acid (LY379268) and 1S,2S,5R,6S-2-aminobicyclo[3.1.0]hexane-2,6-bicaroxylate monohydrate (LY354740)] suggest that these compounds may also directly interact with dopamine (DA) D2 receptors. The current in vitro and in vivo studies were undertaken to further explore this potential interaction with D2 receptors. LY379268 and LY354740 failed to inhibit D2 binding in both native striatal tissue homogenates and cloned receptors at concentrations up to 10 μM. LY379268 and LY354740 (up to 10 μM) also failed to stimulate [35S]GTPγS binding in D2L- and D2S-expressing clones in the presence of NaCl or N-methyl-d-glucamine. In an in vivo striatal D2 receptor occupancy assay, LY379268 (3–30 mg/kg) or LY354740 (1–10 mg/kg) failed to displace raclopride (3 μg/kg i.v.), whereas aripiprazole (10–60 mg/kg) showed up to 90% striatal D2 receptor occupancy. LY379268 (10 mg/kg) and raclopride (3 mg/kg) blocked d-amphetamine and phencyclidine (PCP)-induced hyperactivity in wild-type mice. However, the effects of LY379268 were lost in mGlu2/3 receptor knockout mice. In DA D2 receptor-deficient mice, LY379268 but not raclopride blocked both PCP and d-amphetamine-evoked hyperactivity. In the striatum and nucleus accumbens, LY379268 (3 and 10 mg/kg) was without effect on the DA synthesis rate in reserpinized rats and also failed to prevent S-(−)-3-(3-hydroxyphenyl)-N-propylpiperidine-induced reductions in DA synthesis rate. Taken together, the current data fail to show evidence of direct DA D2 receptor interactions of LY379268 and LY354740 in vitro or in vivo. Instead, these results provide further evidence for a novel antipsychotic mechanism of action for mGluR2/3 agonists.